2017
DOI: 10.1053/j.ajkd.2016.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Cardiothoracic Ratio and All-Cause Mortality and Cardiovascular Disease Events in Hemodialysis Patients: The Q-Cohort Study

Abstract: Higher cardiothoracic ratio is associated with higher risk for both all-cause mortality and CVD events in patients undergoing HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…In fact, CEs have been reported concurrently as the largest single cause of mortality in dialysis patients. [16][17][18] The finding that ASA > 3 is independently associated with CEs is expected since other reports confirm a significant association between comorbidity and adverse postoperative outcomes. [19][20][21][22][23] Findings of our study suggest that perioperative blood transfusions independently increase rates of post-TEVAR CEs; however, this association should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 78%
“…In fact, CEs have been reported concurrently as the largest single cause of mortality in dialysis patients. [16][17][18] The finding that ASA > 3 is independently associated with CEs is expected since other reports confirm a significant association between comorbidity and adverse postoperative outcomes. [19][20][21][22][23] Findings of our study suggest that perioperative blood transfusions independently increase rates of post-TEVAR CEs; however, this association should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 78%
“…However, an autopsy study has reported a satisfactory association between CTR and heart size [ 29 ]. Moreover, some studies have disclosed that CTR had significant association with CV mortality [ 9 , 12 , 14 ] or CV events [ 11 , 13 ] in patients on CHD. Thereafter, an elevated CTR may indicate heart problem in certain extent and then it allows us to use CTR as the surrogate of ventricular remodeling in patients on CHD because CTR is a simple and inexpensive method.…”
Section: Discussionmentioning
confidence: 99%
“…18 years old undergoing HD in 39 dialysis facilities in Saga and Fukuoka Prefectures, Kyushu, Japan. The details of this study have been described previously (14)(15)(16). Patients were enrolled from December 2006 to December 2007.…”
Section: Design Of the Q-cohort Study And Study Populationmentioning
confidence: 99%